Eficacia de un programa de salud bucal para cuidadores de personas con discapacidad - Adum-Lípari, Mirella Narcisa (2024)
Objective: Determine the level of knowledge of caregivers of people with disabilities about oral health before and after applying a program of educational workshops on the subject. Methods: It was a quasi-experimental study of direct intervention, longitudinal, with control before and after, with non-probabilistic sampling. An educational oral health program for caregivers of people with disabilities was developed, applied, and evaluated through a survey before and after its implementation, in 111 caregivers, as well as the evaluation of the Oral Hygiene Index of their relatives with disabilities, in the period from October to December 2020. Results: Before the intervention, 9.9% of people with disabilities attended the dentist every six months, which increased to 76.5%. Before the program, 102 people only used toothbrushes and toothpaste for oral cleaning, after 109 continued using the same products, however, the use of dental floss increased by 7 people. The Oral Hygiene Index remained regular, although it decreased from 2.30 to 1.68. Conclusion: The application of the oral health program had a favorable impact on caregivers, improving the knowledge regarding oral hygiene of their relatives with disabilities, improving the Oral Hygiene Index.